Health concerns related to housing, sanitation, water access and waste disposal in a poor mixed urban community, Mbekweni in Paarl - Ngakane, Lerato (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPhil)--Stellenbosch University, 2021.